WHF Position Statement on COVID Vaccination - F. Thienemann; G. Chakafana; D. Piñeiro; F. J. Pinto; P. Perel; K. Singh; J.-L. Eiselé; D. Prabhakaran; K. Sliwa (Ubiquity Press, 2021)
The current COVID-19 pandemic has challenged health systems and communities globally. As such, several countries have embarked on national COVID-19 vaccination programmes in order to curb spread of the disease. However, at present, there isn't yet enough dosages to enable vaccination of the general population. Different vaccine prioritization strategies are thus being implemented in different communities in order to permit for a systematic vaccination of individuals. Here, on behalf of the World Heart Federation, we emphasize the need for individuals with Cardiovascular disease to be prioritized in national vaccine prioritization programmes as these are high risk individuals.